PENGARUH LATIHAN FARTLEK TERHADAP KEMAMPUAN DAYA TAHAN PEMAIN FUTSAL SMA TITIAN TERAS JAMBI DALAM PERTANDINGAN - Frans Jonathan Yabez Siahaan; Ahmad Muzaffar; Fitri Khairunnisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The background of this research is based on field issues indicating that many members of the futsal extracurricular team at SMA Titian Teras Jambi are still unable to maintain stamina and play at a fast intensity for extended periods during matches. This study aims to analyze the effect of implementing the fartlek training method on improving the performance and endurance capabilities of futsal players at SMA Titian Teras Jambi during matches. The method used in this research is a quantitative method with an experimental approach. The applied research design is a Two-Group Pre-test and Post-test Design. The population in this study consists of all 25 players in the futsal extracurricular program at SMA Titian Teras Jambi. The sampling technique utilizes a total sampling or saturated sampling method. Data collection for cardiorespiratory endurance capacity was measured using the Bleep Test instrument. The fartlek intervention training program was administered to the experimental group over a 6-week period with a frequency of two sessions per week. Data analysis techniques used include analysis prerequisite tests (normality and homogeneity tests) as well as hypothesis testing using a t-test to observe significant differences between the pre-test and post-test results This research is motivated by field observations showing that many futsal extracurricular team members at SMA Titian Teras Jambi struggle to maintain stamina and sustain high-intensity play throughout a match. This study aims to analyze the impact of the fartlek training method on enhancing the performance and endurance of these players. A quantitative method with an experimental approach was employed, specifically utilizing a Two-Group Pre-test and Post-test Design. The study's population comprised all 25 members of the SMA Titian Teras Jambi futsal extracurricular team, selected via total (saturated) sampling. Cardiorespiratory endurance data were gathered using the Bleep Test. The experimental group underwent a 6-week fartlek training intervention, meeting twice a week. Data analysis involved prerequisite testing (normality and homogeneity tests) and hypothesis testing via a t-test to determine significant differences between pre-test and post-test outcomes.